2019
DOI: 10.1097/gox.0000000000002355
|View full text |Cite
|
Sign up to set email alerts
|

Acellular Dermal Matrix Sterility: Does It Affect Microbial and Clinical Outcomes Following Implantation?

Abstract: Introduction:The use of acellular dermal matrices (ADMs) in breast reconstruction is a controversial topic. Recent literature has investigated the effects of ADM sterilization on infectious complications, although with varying conclusions. Previous work by our group showed no difference between aseptic and sterilized products immediately out of the package. In this study, we investigate the microbiologic profiles of these agents after implantation.Methods:In this prospective study, we cultured samples of ADM p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…10,11 However, literature examining infectious outcomes in sterile versus aseptic ADM have produced mixed results, with some citing improved outcomes with the use of sterile products and others reporting no difference. [31][32][33] The identification of minor differences in postoperative complications between the ADM and no-ADM groups in our study, along with recent studies affirming these results, suggest that a more judicious application of ADM in tissue expander placement may be warranted. Proponents of ADM cite aesthetic benefits in the final reconstruction as a rationale for its use including reduced incidence of capsular contracture, decreased occurrences of implant displacement, enhanced lower pole curvature, and greater definition of the inframammary and lateral mammary folds.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…10,11 However, literature examining infectious outcomes in sterile versus aseptic ADM have produced mixed results, with some citing improved outcomes with the use of sterile products and others reporting no difference. [31][32][33] The identification of minor differences in postoperative complications between the ADM and no-ADM groups in our study, along with recent studies affirming these results, suggest that a more judicious application of ADM in tissue expander placement may be warranted. Proponents of ADM cite aesthetic benefits in the final reconstruction as a rationale for its use including reduced incidence of capsular contracture, decreased occurrences of implant displacement, enhanced lower pole curvature, and greater definition of the inframammary and lateral mammary folds.…”
Section: Discussionsupporting
confidence: 71%
“…10,11 However, literature examining infectious outcomes in sterile versus aseptic ADM have produced mixed results, with some citing improved outcomes with the use of sterile products and others reporting no difference. 31–33…”
Section: Discussionmentioning
confidence: 99%
“…In viewing ADM burden as a dose-response relationship to infection, in this setting of increased quantity of ADM burden, it is no surprise that infection rates were 5 times greater in this patient population. The literature examining the microbiologic properties and clinical outcomes between aseptic and sterilized ADM has had mixed results, with some citing no differences while others suggest improved outcomes with sterile ADM. 16,23,24 Surgical technique for total wrap can vary between providers. At our institution, typically the entirety of the implant, both anterior and posterior, is draped with the uniform piece of ADM.…”
Section: Discussionmentioning
confidence: 99%
“…Buseman et al [ 19 ] reported significantly higher seroma rates in the sterile AlloDerm ready-to-use (RTU; LifeCell Corporation, Branchburg, NJ, USA) group (P=0.003) than in the aseptic AlloDerm freeze-dried (FD; LifeCell Corporation) group, but no differences in infection rates. In a similar context, in a prospective study by Klein et al [ 20 ], ADM samples from the first stage of tissue expander-based immediate breast reconstruction were cultured. No growth was found in any cultures, leading the authors to question the need for terminal sterilization of ADM.…”
Section: Discussionmentioning
confidence: 99%